Harmonisation of laws on inheritance between Muslim and non-Muslim subjects - Drs Nasrul, Muhammad Amrullah; Mohd Alam Shah, Nurin Athirah; Abdul Manaf, Zati Ilham; Muhamad Ibrahim, Najhan (Centre for Islamisation, International Islamic University Malaysia, 2024)
Inheritance is a matter that needs to be prioritised by the living when there is an occurrence of death. Nowadays, the society in Malaysia is aware of the importance of inheritance. Among the general rules under inheritance is that the inheritance of Muslims is subject to distribution by faraid. As for non-Muslims, the division of inheritance needs to be carried out by the Distribution Act 1958. The difference in inheritance management and distribution between Muslims and non-Muslims is clear due to the differences in laws that govern the matter. However, when it involves non-Muslims who convert to Islam or are referred to as muallaf, the process of inheritance is a bit different, especially in cases when the converted deceased left non-Muslim heirs. In this study, the researcher employs a qualitative approach, by conducting library-based research on the relevant materials including, but not limited to statutory provisions, case laws, textbooks, journal articles, newspapers, conference proceedings, and seminar papers. Based on the findings, it is difficult to resolve inheritance issues involving muallaf and this may result in a conflict of power between the Syariah Court and Civil Court. To overcome this issue, it is suggested that a clear guideline in dealing with muallaf needs to be enforced in order to harmonise the laws on inheritance between Muslims and non-Muslims.